Onset of convection in a sparsely packed porous layer with throughflow (Archives of Mechanics - Test, 2001)
The onset of Rayleigh-Bénard convection in a sparsely packed porous layer with vertical throughflow is investigated using Brinkman's modification of the Darcy flow model with fluid viscosity different from effective viscosity. The critical Rayleigh numbers are obtained for free-free, rigid-rigid and rigid-free boundaries which are insulated to temperature perturbations. It is noted that an increase in the value of viscosity ratio is to delay the onset of convection. Further, it is observed that the throughflow can be used either to suppress or augment convection, depending on the nature of boundaries and also on the values of physical parameters.